Toilet Training Fosters Self-Confidence and Independent Habits in Early Childhood - Eva Z`ulita; Siti Mayang Sari; Mhd. Syafii (Aulad: Journal on Early Childhood, 2026)
Toilet training is an important developmental milestone in early childhood that supports the development of self-confidence and independent habits. This study aims to examine the role of toilet training in fostering independence, self-control, and emotional development in young children. The study employed a qualitative descriptive approach through observations and interviews with early childhood educators and parents to explore changes in children’s behavior during the toilet training process. The results show that implementing toilet training in accordance with children’s developmental stages can enhance self-confidence, encourage independence in maintaining personal hygiene, and foster responsibility for self-care activities. Supportive guidance and positive reinforcement from adults significantly influence children’s success and emotional readiness in undergoing toilet training. Toilet training involves both the acquisition of physical skills and an educational process that contributes to character development and the formation of independent habits in early childhood through the collaborative roles of parents and teachers.